Transformation of children's paintings into public art to improve public spaces and enhance peoples happiness - Luo, Na; Ibrahim, Rahinah; Zainal Abidin, Sazrinee (MDPI, 2022)
Characteristics of children’s paintings have been suggested considered for application in public art since they are known to positively evoke a sense of well-being when people see them. This study aims to understand the impact of artistic features from children’s drawings on people’s well-being; then analyzing the adaptive design principles of 3D public art featuring children’s paintings on people’s happiness; and finally, exploring the influence of 3D public art featuring children’s paintings on improving public spaces and enhancing people’s well-being. The results lead to proposing a conceptual framework for public artworks in public spaces for improving people’s happiness. The proposed conceptual framework recommends that, by applying the visual and thinking features of children’s paintings to public art, artists can design high-quality artworks suitable for a city, which could improve people’s happiness in public spaces. This study recommends further research into how public art can promote public spaces and shape the urban culture. It contributes to enhancing the quality of public art and public spaces, and inspiring a sense of well-being among citizens through the use of appropriate public art. The results are significant because they will help artists to create more high-quality public artworks for urban public spaces in order to evoke people’s happiness.